A multi-proxy study of changing environmental conditions in a Younger Dryas sequence in southwestern Manitoba, Canada, and evidence for an extraterrestrial event. Issue 1 (January 2020) - Teller, James; Boyd, Matthew; LeCompte, Malcolm; Kennett, James; West, Allen; Telka, Alice; Diaz, Aura; Adedeji, Victor; Batchelor, Dale; Mooney, Charles; Garcia, Roberto
Abstract: Multi-proxy analyses of a sequence spanning the Younger Dryas (YD) in the Glacial Lake Hind basin of Manitoba provides insight into regional paleohydrology and paleovegetation of meltwater rivers and lakes spanning >4000 yr; the sequence is controlled by 25 new accelerator mass spectrometry ages. This lake, dammed by the Laurentide Ice Sheet, overflowed into Lake Agassiz. The pre-YD interval records rapid sedimentation from meltwaters that headed in proglacial lakes in the Canadian Prairies that are known to have been catastrophically released when ice or sediment barriers were breached. Pollen in this phase is dominated by pre-Quaternary forms eroded from Paleocene bedrock. At the onset of the YD at 12.8 cal ka, the sudden appearance of concentrations of nanodiamonds, high-temperature magnetic spherules, platinum, and iridium provide evidence of an extraterrestrial (ET) event that others have identified at more than 40 sites in North America. Major changes in oceans and climate, and the catastrophic outflow of nearby Lake Agassiz at the onset of the YD, may be related. Lower water levels and a reduction of Souris River inflow to Lake Hind followed, which are reflected by more clayey and organic-rich sediments and a decrease in pre-Quaternary palynomorphs. This may have resulted from the deepening of river valleys caused by the release of meltwater triggered by the ET event. Wetlands then began to develop, leading to peat deposition from 12.3 to 11 cal ka. This was followed by a fluvial episode depositing sand and then by increased Holocene aridity that resulted in accumulation of a thick sequence of dune sands. A dry woodland environment with a mix of conifers (especially Picea and Larix ) and deciduous trees (especially Populus and Quercus ) covered the uplands from 13 to 10 cal ka.